Imaging of Vascular Anomalies - Gayou, Edward; Chau, Alex; Josephs, Shellie (Seminars in Interventional Radiology, 2024)
Vascular anomalies (VAs) are a heterogeneous group of vascular malformations and tumors that are frequently encountered in daily practice. While most are benign, malignant vascular tumors exist, as do other nonvascular soft-tissue malignancies that may masquerade as a benign VA. The subtleties of arriving at an accurate diagnosis can be intimidating, as new entities are described and names of conditions have been modified. Therefore, the goal of this article is to describe the classic imaging findings of VAs so that the interventional radiologist can confidently and competently contribute to management decisions, with special attention to ominous imaging features that should prompt biopsy or further imaging workup.
Keywords: interventional radiology; vascular anomalies; arteriovenous malformations; venous malformations; tumors